A Participatory Job Crafting Intervention to Enhance Teachers’ Quality of Work Life in a Multicultural International School Context - Lely Nur Azizah; Umi Anugerah Izzati; Meita Santi Budiani; Olievia Prabandini Mulyana; Sukmawati Puspitadewi Ni Wayan (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Teachers’ quality of work life (QWL) plays a significant role in sustaining instructional effectiveness, particularly in international school settings characterized by multicultural dynamics and complex institutional demands. This study explored teachers’ perceptions of quality of work life following the implementation of a job crafting training program at Sekolah Indonesia Johor Bahru (SIJB), Malaysia. The intervention was conducted using a Participatory Action Research (PAR) approach involving 24 teachers and implemented through iterative cycles of planning, action, observation, and reflection. Qualitative data were collected through semi-structured interviews, classroom observations, reflective worksheets, and group discussions, and analyzed using thematic analysis. The findings revealed patterns consistent with the dimensions of task, relational, and cognitive crafting. Teachers described shifts toward more intentional instructional adaptation, enhanced professional collaboration, and a reframing of work meaning and professional identity. These perceived changes suggest that job crafting functioned as a reflective framework enabling teachers to reinterpret and reorganize existing responsibilities within a multicultural educational environment. The participatory structure of the intervention appeared to strengthen teachers’ sense of agency and contextual relevance. However, the findings reflect short-term interpretive experiences and do not establish long-term behavioral sustainability. This study contributes contextually grounded insights into how job crafting, when embedded within a participatory framework, may support teachers’ perceived quality of work life in international school contexts.